Regioselective Palmitoylation of 9-(2,3-Dihydroxy- propyl)adenine Catalyzed by a Glycopolymer-enzyme Conjugate - Brabcová, Jana; Blažek, Jiří; Krečmerová, Marcela; Vondrášek, Jiří; Palomo, Jose M; Zarevúcka, Marie (Molecules (Basel, Switzerland), 2016)
The enzymatic regioselective monopalmitoylation of racemic 9-(2,3-dihydroxypropyl)- adenine (DHPA), an approved antiviral agent, has been performed by an immobilized form of Candida antarctica B lipase (CAL-B) using a 4:1 DMF/hexane mixture as the reaction medium. To improve the chemical yield of the desired monopalmitoylation reaction, solid-phase chemical modifications of the lipase were evaluated. The reaction yield was successfully increased obtaining 100% product after a second treatment of the product solution with fresh immobilised chemically glycosylated-CAL-B.
Keywords: hexany; lipoylace; Adenine; katalýza; enzymy imobilizované; Enzymes, Immobilized; lipasa; Stereoisomerism; Catalysis; Hexanes; adenin; Lipoylation; fungální proteiny; regioselectivity; glykosylace; Polymers; Glycosylation; stereoizomerie; Fungal Proteins; glycosylation; rozpouštědla; Lipase; palmitoylation; Solvents; polymery; chemical modification; Candida